Islamic Pension Funds in Indonesia: A Utilitarian Perspective on Post-P2SK Regulatory Reform - Hanim, Salwa Faeha (Information Technology and Science (ITScience), 2025)
Pension fund management and regulation require flexibility and legal certainty to maximize pension benefits. Investment instruments in Islamic pension funds are still limited to normative aspects, limiting their development to specific investments. The purpose of this study is to analyze how Islamic pension funds are managed, both in terms of regulation and the innovation of investment instruments, over the last two years following the enactment of Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector. The research methodology used is qualitative research and library research, which involves collecting scientific data and information, including legal Theory, specifically Jeremy Bentham's Theory of utilitarianism, which serves to assess the benefits of regulatory reform. Furthermore, this study employs a legal approach, collecting legal documents such as laws, journals, and books to analyze the management and development of Islamic pension funds in Indonesia. This study concludes that Islamic pension funds are already regulated under Financial Services Authority Regulation No. 33/POJK.05/2016 concerning the Implementation of Pension Programs Based on Sharia Principles and Portfolio. Islamic investment instruments that were already available for managing Islamic pension funds, even before POJK No. 33/POJK 05/2016 was issued, include mudharabah deposits, Islamic stocks, Islamic mutual funds, and Islamic bonds. The study shows that, following the enactment of Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector and Financial Services Authority Regulation No. 27 of 2023 concerning the Implementation of Pension Fund Businesses, there has been a significant shift from formal compliance supervision to risk-based supervision. The latest regulations provide room for innovation by expanding the choice of instruments and enabling more flexible operational mechanisms. From a utilitarian perspective, the latest regulations in Indonesia demonstrate measurable legal benefits that strengthen the Islamic pension fund sector.